Evaluation of Antibacterial Activity of Crude Aqueous, Ethanolic and Methanolic Leaf Extracts of Piper retrofractum Vahl. and Piper betle L. - Jamelarin, Emily Mesa; Balinado, Lloyd Ongpauco (Asian Journal of Biological and Life Sciences, 2019)
Piper retrofractum and P. betle are commonly used as medicinal plants in the Philippines to treat several ailments, including headache, fever, stomachache, cough, cuts, and wounds. To determine how effective these plants are in treating microbial-caused ailments, this study was conducted. This primarily aimed to investigate the antibacterial activities of the crude aqueous, ethanolic, and methanolic leaf extracts of these two plants using disc-diffusion assay and resazurin-based microtiter broth dilution method. Antibacterial tests against Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus showed that ethanolic and methanolic leaf extracts of P. betle had the highest zone of inhibition (i.e., 17.67 mm) against E. coli and S. aureus, respectively. The same was exhibited by methanolic extract of P. retrofractum against S. aureus. Maximum antibacterial activity was then recorded for methanolic and ethanolic leaf extracts of P. betle against E. coli and S. aureus, respectively, at a Minimum Inhibitory Concentration (MIC) of 0.59 mg/mL. These results support the efficacy of these plants in treating skin and gastrointestinal diseases caused by S. aureus and E. coli, correspondingly.
Keywords: Antibacterial; Disk diffusion assay; Microtiter broth dilution; Minimum inhibitory concentration; Piper betle; Piper retrofractum